1992
DOI: 10.1007/bf00918150
|View full text |Cite
|
Sign up to set email alerts
|

Chronic enteroviral meningoencephalitis in agammaglobulinemia: Case report and literature review

Abstract: Chronic enteroviral meningoencephalitis is a well-recognized complication in patients with X-linked agammaglobulinemia (XLA). The majority of published cases refers to its occurrence in patients on no replacement therapy or on only intramuscular immunoglobulin. The advent of intravenous immunoglobulin (IVIg) in the early 1980s and its widespread use in XLA was thought to have virtually eradicated enteroviral meningoencephalitis in these patients. We describe the development of echovirus meningoencephalitis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(78 citation statements)
references
References 19 publications
1
76
0
Order By: Relevance
“…NI, Not infected; ST2, T1/ST2. Because Abs are essential for viral clearance during enteroviral infection (26,27), we first determined the levels of CVB5-specific Abs in infected WT and T1/ST2 2/2 mice. We found that T1/ ST2 2/2 mice produced more serum anti-CVB5 IgG and IgM than WT mice (Supplemental Fig.…”
Section: Il-33 Is Produced Post Cvb5 Infection and Is Essential For Tmentioning
confidence: 99%
“…NI, Not infected; ST2, T1/ST2. Because Abs are essential for viral clearance during enteroviral infection (26,27), we first determined the levels of CVB5-specific Abs in infected WT and T1/ST2 2/2 mice. We found that T1/ ST2 2/2 mice produced more serum anti-CVB5 IgG and IgM than WT mice (Supplemental Fig.…”
Section: Il-33 Is Produced Post Cvb5 Infection and Is Essential For Tmentioning
confidence: 99%
“…High-pressure liquid chromatographypurified (Ͼ95% pure) major histocompatibility complex (MHC) class I peptides GP [33][34][35][36][37][38][39][40][41] (KAVYNFATM) and NP 396-404 (FQPQNGQFI) were purchased from Peptidogenic (Livermore, Calif.). Spleen cells (2 ϫ 10 6 per well) from virusinfected mice were stimulated with 10 Ϫ7 M peptide in the presence of 2 g/ of brefeldin A (Sigma, St. Louis, Mo.)…”
Section: Intracellular Cytokine Staining (Iccs)mentioning
confidence: 99%
“…Antibodies are important in eradicating enteroviruses, and agammaglobulinemic humans are susceptible to chronic infections with polioviruses (26), echoviruses (35,38), and coxsackieviruses (16,20). However, T cells also play a role in limiting viral titers (18,55), and antibodies appear to contribute little to the protection induced by a CVB DNA vaccine (19), suggesting that virus-specific memory T cells might be important in vaccine-induced immunity.…”
mentioning
confidence: 99%
“…and with virus being cleared by the adaptive immune response (17). However, enterovirus infections can persist under conditions of immunodeficiency (48,51,65,71). Infectious enteroviruses are frequently isolated from pediatric cases of human myocarditis, but isolation from adult cases of the disease has been exceedingly rare (34,62,88), perhaps because pediatric cases may be more likely to be diagnosed during the acute infection.…”
mentioning
confidence: 99%